A novel approach to first‐trimester screening for early pre‐eclampsia combining serum PP‐13 and Doppler ultrasound - K. H. Nicolaides; Randy Bindra; Özhan Turan; Ilana Chefetz; Marei Sammar; Hamutal Meiri; J. Tal; Howard Cuckle (2005)
Abstract Objective To investigate the value of maternal serum placental protein 13 (PP‐13) measurement and uterine artery Doppler during first‐trimester screening in the prediction of early pre‐eclampsia. Methods This was a nested case‐control prospective study of pregnancies at 11 + 0 to 13 + 6 weeks of gestation. The pulsatility index (PI) of blood flow in the uterine arteries and the maternal serum concentration of PP‐13 were measured in 10 women who went on to develop pre‐eclampsia that necessitated delivery before 34 weeks, and in 423 unaffected women. Results were expressed as multiples of the gestation‐specific median in controls (MoM). A logistic regression model was used to predict detection and false‐positive rates. Results In the cases that developed pre‐eclampsia requiring delivery before 34 weeks, compared with the unaffected pregnancies, the median uterine artery PI was higher (1.43 MoM) and the median serum PP‐13 level was lower (0.07 MoM; P < 0.001, Wilcoxon rank sum test for both). Modeling predicted that for a 90% detection rate of pre‐eclampsia requiring delivery before 34 weeks, the false‐positive rate of screening by PP‐13 was 12%, by uterine artery PI was 31% and by a combination of the two methods was 9%. A policy of contingency screening, whereby all women are screened by maternal serum PP‐13 and only the 14% at highest risk are then screened by Doppler, achieved a detection rate of 90% with an overall false‐positive rate of 6%. Conclusion Effective screening for pre‐eclampsia requiring delivery before 34 weeks can potentially be provided by assessment of a combination of maternal serum PP‐13 and uterine artery Doppler in the first trimester of pregnancy. Copyright © 2005 ISUOG. Published by John Wiley & Sons, Ltd.